Efficiency, Distortions and Factor Utilization during the Interwar Period - Alex Klein; Keisuke Otsu (University of Kent, School of Economics, 2013)
In this paper, we analyze the International Great Depression in the US and Western Europe using the business cycle accounting method a la Chari, Kehoe and McGrattan (CKM 2007). We extend the business cycle accounting model by incorporating endogenous factor utilization which turns out to be an important transmission mechanism of the disturbances in the economy. Our main findings are that in the US labor wedges account for roughly half of the drop in output while efficiency and investment wedges each account for a quarter of it during the 1929-1933 period while in Western Europe labor wedges account for more than one-third of the output drop and efficiency, government and investment wedges are responsible for the remaining during the 1929-1932 period. Our findings are consistent with several strands of existing descriptive and empirical literature on the International Great Depression.
Keywords: E13; E32; N10; 330; International Great Depression; Business Cycle Accounting; Efficiency; Market Distortions